MUSA ACUMINATA, CITRUS LEMON AROMATHERAPY, PC6 POINT OF ACUPUNCTURE TOWARD EMESIS GRAVIDARUM - Ilmiah, Widia Shofa; Abdullah, Ikhwan; Sulistiyah, Sulistiyah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2026)
The prevalence rate of emesis gravidarum in the world is 15%, in Indonesia is 10% in all pregnancies. The results of preliminary studies at Independent Midwifery Practice Sumariyah on February 20, 2024 by interviewing 62 pregnant women the 1st trimester amount of 35 pregnant women (56.4%) experiencing emesis gravidarum. Analyze effectivity of Musa Acuminata, Citrus Lemon Aromatherapy, PC6 Point Acupuncture toward Frequency of Emesis Gravidarum. Quasy Experimental Non-Equivalent Control Group design. Accidental sampling technique, samples 16 intervention groups; 16 control groups. Data collection techniques with measure emesis gravidarum before and after 24 hours at aboth group. Instruments using PUQE 24 score questionnaire, observation sheet, pamphlet. Data analysis using Wilcoxon. After being administration in the intervention group known decrease of intensity of nausea vomiting from 4-6 times becomes 1-3 times (25.0%). After being placebo in control group known still nausea vomiting between 4-6 times (62.5%). P value =0.021 in the intervention group; p=0.317 in the control group. Intervention of administration of Musa Acuminata, Citrus Lemon Aromatherapy, PC6 Point Acupuncture “de qi” technique in the intervention group is known effective in reducing the frequency of nausea vomiting immediately compared to the control group.